Reconfigurable Multiprocessor Systems: A Review. (28th October 2010) - Dorta, Taho; Jiménez, Jaime; Martín, José Luis; Bidarte, Unai; Astarloa, Armando
Abstract : Modern digital systems demand increasing electronic resources, so the multiprocessor platforms are a suitable solution for them. This approach provides better results in terms of area, speed, and power consumption compared to traditional uniprocessor digital systems. Reconfigurable multiprocessor systems are a particular type of embedded system, implemented using reconfigurable hardware. This paper presents a review of this emerging research area. A number of state-of-the-art systems published in this field are presented and classified. Design methods and challenges are also discussed. Advances in FPGA technology are leading to more powerful systems in terms of processing and flexibility. Flexibility is one of the strong points of this kind of system, and multiprocessor systems can even be reconfigured at run time, allowing hardware to be adjusted to the demands of the application.